PENDIDIKAN KARAKTER QUR’ANI DALAM PERSPEKTIF PENGASUH PONDOK PESANTREN PUTRI 1 AL-AMIEN PRENDUAN - Najmi Faza; Nailatur Rohmah (CV Putra Publisher, 2023)
Education is defined as a means of civilizing and distributing values that can shape a better character. Character education aims to form moral, intelligent, rational, innovative, hard-working, optimistic, and confident human beings. Qur'anic character is a character that must be instilled in every child. Islamic boarding school is an environment that is able to build the Qur'anic character of every child because boarding school is an educational institution that upholds religious values. This article describes the Quranic character education applied in a islamic boarding school. This study uses a qualitative approach to the type of phenomenology, which is located at girls islamic boarding school 1 of Al-Amien Prenduan. The data obtained are based on two sources, namely primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. Data analysis used is data reduction, data presentation, and drawing conclusions or verification. Furthermore, checking the validity of the data by extending observations, triangulation. The results of this study are: The caregive of the girls Islamic boarding school 1 of Al-Amien Prenduan has a very important role in Qur'ani character education. student. Qur'anic character education what the caregivers do to the female students in this boarding school uses several concepts, namely imitating the Prophet Muhammad, exemplary and habituation. This aims to make female students have good morals in line with the moral values contained in the holy book Al-Qur'an.